Pengaruh Penggunaan Gadget terhadap Minat Baca Peserta Didik di SMAN 1 Tolitoli - Cindi Amalia Hapsari; Mohammad Djamil M Nur; Arda Arda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the influence of the use of gadgets on the reading interest of students at SMAN 1 Tolitoli. The background of this research departs from the phenomenon of declining students' interest in reading in the digital era, where students spend more time using gadgets for entertainment such as social media, online games, and watching videos than reading books or lesson literature. The low number of visits to school libraries, which only increased before the exam, is a major indicator of the weakening of the literacy culture among students. This study uses a quantitative approach with data collection techniques through observation, questionnaires, and documentation. Data analysis was carried out by normality test, t-test, and determination coefficient (R²) to determine the magnitude of the influence of gadgets on reading interest. The results of the study show that there is a significant influence between the use of gadgets on students' reading interest. The tcalculated value of 4,028 > ttable 1,655 indicates that H₀ is rejected and Hₐ is accepted. The use of gadgets contributed 9.8% to the reading interest of students at SMAN 1 Tolitoli, while the rest was influenced by other factors such as family environment, learning motivation, and support for literacy facilities at school.